Framing Kemanusiaan TNI AD dalam Konten Bantuan Erupsi Gunung Lewotobi di Instagram - Rizqi Akmaliah; Esfandani Peni Indreswari; Rahmat Wisudawanto (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The development of social media has transformed institutional communication strategies, including those of the Indonesian Army (TNI AD) in building a more humanized image. This study aims to analyze how visual and narrative elements in the disaster relief content related to the eruption of Mount Lewotobi, as published by TNI AD on Instagram, are constructed and conveyed to the public. The research employs a qualitative descriptive method using Robert N. Entman’s framing analysis model, which includes problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were collected through observation and documentation of TNI AD’s Instagram post dated January 13, 2024. The findings indicate that both visual and narrative framing effectively shape public perception of the TNI AD as a responsive, compassionate, and empathetic emergency actor that presents itself as a solution during humanitarian crises. The humanistic image is emphasized through visuals depicting aid distribution, warm interactions with residents, and the provision of healthcare services. The implications of this study suggest that social media can serve as a strategic tool to strengthen public trust and expand the military's communication role in the civilian sphere, particularly during disaster situations.